Evidence of B+ → [tau]+ [nu] decays with hadronic B tags - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We present a search for the decay B+→τ+ν using 467.8×106 B¯¯¯B pairs collected at the Υ(4S) resonance with the BABAR detector at the SLAC PEP-II B-Factory. We select a sample of events with one completely reconstructed B− in the hadronic decay mode (B−→D(*)0X− and B−→J/ψX−). We examine the rest of the event to search for a B+→τ+ν decay. We identify the τ+ lepton in the following modes: τ+→e+ν¯ν, τ+→μ+ν¯ν, τ+→π+¯ν and τ+→ρ+¯ν. We find an excess of events with respect to the expected background, which excludes the null signal hypothesis at the level of 3.8σ (including systematic uncertainties) and corresponds to a branching fraction value of B(B+→τ+ν)=(1.83+0.53−0.49(stat)±0.24(syst))×10−4.